ANALISIS RISIKO KECELAKAAN KERJA DENGAN METODE HIRARC PADA PROYEK PEMBANGUNAN SKY BRIDGE REVO TOWN TAHUN 2022 - Aisyah Amelia Surahman (2022)
Hazard Identification Risk Assessment and Risk Control (HIRARC) is a process of hazard identification, risk assessment to determine the high or low value of a risk so as to assist in the control process. This study was conducted to analyze the risk of work accidents using the HIRARC method on the Revo Town Sky Bridge Construction Project. This type of research is qualitative, the research begins with the classification of activities contained in the Revo Town Sky Bridge Construction Project, which is then identified by hazards in each work so that the source of the hazard that is waiting for will be assessed using a risk assessment using the HIRARC method. The classification of work in the Sky Bridge Construction Project is Structural, Architectural, Mechanical, Electrical and Plumbing Work, in Architectural work there are 4 work activities, namely ceramic installation, sandwich installation, stainless railing installation, and ACP ceiling installation. The risk value in the Revo Town Sky Bridge Construction Project is as much as 26% (18 sources of danger) have a high level of risk, then 30% (21 sources of danger) have a moderate level of risk, and as many as 44% (30 sources of danger) have a risk minor work accident. Keywords: Construction, HIRARC, Risk Assessment.